2004
DOI: 10.1007/s11881-004-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological awareness in developmental dyslexia

Abstract: This study examines morphological awareness in developmental dyslexia. While the poor phonological awareness of dyslexic children has been related to their difficulty in handling the alphabetical principle, less is known about their morphological awareness, which also plays an important part in reading development. The aim of this study was to analyze in more detail the implications of the phonological impairments of dyslexics in dealing with larger units of language such as morphemes. First, the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
176
0
30

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(231 citation statements)
references
References 28 publications
19
176
0
30
Order By: Relevance
“…In this study, we will retrospectively reclassify these participants based on literacy difficulties that were observed in second grade to determine MA deficits' relation to the behaviorally observed literacy difficulties across time. Based on the findings of Law et al, (2016) demonstrated early MA deficits of high-risk children along with past research showing MA deficits in poor and dyslexic readers later in life (Casalis, Colé, & Sopo, 2004;Fowler, Liberman, & Feldman, 1995;Law, et al, 2015, Robertson, Joanisse, Desroches, & Terry, 2012Tsesmeli & Seymour, 2006), we expect to find an association between literacy difficulties and MA deficits across all time points of this longitudinal study, from kindergarten to second grade.…”
Section: The Present Studymentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, we will retrospectively reclassify these participants based on literacy difficulties that were observed in second grade to determine MA deficits' relation to the behaviorally observed literacy difficulties across time. Based on the findings of Law et al, (2016) demonstrated early MA deficits of high-risk children along with past research showing MA deficits in poor and dyslexic readers later in life (Casalis, Colé, & Sopo, 2004;Fowler, Liberman, & Feldman, 1995;Law, et al, 2015, Robertson, Joanisse, Desroches, & Terry, 2012Tsesmeli & Seymour, 2006), we expect to find an association between literacy difficulties and MA deficits across all time points of this longitudinal study, from kindergarten to second grade.…”
Section: The Present Studymentioning
confidence: 54%
“…Research across a multitude of languages and age groups has found that dyslexics often underperform across a variety of measures of MA when compared with chronologically age-matched peers while, at the same time, being found to perform similar to or better than younger reading age-matched controls (Casalis, Colé, & Sopo, 2004;Fowler, Liberman, & Feldman, 1995;Robertson, Joanisse, Desroches, & Terry, 2012;Tsesmeli & Seymour, 2006). These findings suggest that MA deficits are not causal to dyslexic's reading struggles and may be a consequence of poor reading experience or a more primary deficit, like the phonological deficit often associated with dyslexia.…”
Section: Morphological Awarenessmentioning
confidence: 99%
“…It is well established that morphological awareness can predict progress in reading and spelling independently from phoneme awareness (Siegel, 2008) and that training in morphological awareness can improve literacy outcomes (Bowers, Kirby, & Deacon, 2010; Goodwin & Ahn, 2013). However, it is also known that there is a close association between phonological awareness and morphological awareness (Casalis, Colé, & Sodo, 2004; Cunningham & Carroll, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Children with dyslexia have been shown to perform below chronological-age-(CA-) matched peers on morphological awareness measures in many languages (Berthiaume & Daigle, 2014;Carlisle, 1987;Casalis et al, 2004;Duranovic, Tinjak, & Turbic-Hadzagic, 2014;Egan & Pring, 2004;Egan & Tainturier, 2011;Joanisse, Manis, Keating, & Seidenberg, 2000;Leong, 1999;McBride-Chang et al, 2008;McBride-Chang, Liu, Wong, Wong, & Shu, 2012;Shu, McBride-Chang, Wu, & Liu, 2006;Siegel, 2008;Tsesmeli & Seymour, 2006;Vogel, 1977). They have also been shown to use morphological processes (in reading and spelling) less than age-matched peers Carlisle, Stone, & Katz, 2001;Fisher, Shankweiler, & Liberman, 1985;Hauerwas & Walker, 2003;Leong, 1989).…”
mentioning
confidence: 99%
“…To examine whether children with dyslexia show atypical morphological processing given their level of literacy skills, a better comparison is against younger, reading-ability-matched peers. For the most part, children with dyslexia perform similarly to reading-ability-matched children on oral measures of morphological awareness (Casalis et al, 2004;Egan & Pring, 2004;Egan & Tainturier, 2011;Robertson, Joanisse, Desroches, & Terry, 2012;Tsesmeli & Seymour, 2006). However, the picture for morphological processing is less clear.…”
mentioning
confidence: 99%